Hypoglycemia secondary to insulinoma masking the onset of type 1 diabetes in an adolescent. Issue 9 (24th September 2021) - Subramani, Sriya; Bellizzi, Andrew M.; Borcherding, Nicholas; Kao, Simon C.; Dillon, Joseph; Howe, James; Norris, Andrew W.; Tansey, Michael J.; Pinnaro, Catherina T.
Abstract: Type 1 diabetes and insulinoma can co‐occur in pediatric patients and may present with episodes of hypo‐ and hyperglycemia, significant glycemic variability, and weight gain. Surgical resection leads to development of fulminant diabetes. Abstract : Type 1 diabetes and insulinoma can co‐occur in pediatric patients and may present with episodes of hypo‐ and hyperglycemia, significant glycemic variability, and weight gain. Surgical resection leads to development of fulminant diabetes.